Testicular tuberculous mimicking malignant tumor of testis: a diagnostic and surgical dilemma - Hadi, Shamsul (International Journal of Pathology, 2023)
Background: Clinically Orchitis may resemble malignancy. Our objective is to determine importance of multidisciplinary approach to diagnose testicular Tuberculosis (TB). Material and Methods: A 27-year young male from Afghanistan presented with 2 weeks history of left scrotal swelling. FNAC, Zeil Nelson stain, MTB-PCR done for diagnosis as clinically it mimics malignancy. Results: Cytopathological finding were chronic granulomatous changes with suppurative acute inflammation. ZN stain was positive for AFB. The diagnosis was confirmed by MTB-PCR and gene expert. Conclusion: It indicates that multidisciplinary approach is important for diagnostic accuracy, optimal treatment and avoiding needless surgical intervention in case of testicular TB.